Election Night as Bruce Bronzan Wins 31st Assembly District Primary - Watkins, Howard::::::::: (1982)
? And Bruce Bronzan in front of old Fresno photograph Photograph shows automobiles, streetcar, and horse drawn wagon on Mariposa Street with Courthouse and Hughes Hotel in background